A ROLE OF PUNARNAVADI KSHIR BASTI AND PUNARNAVADI KWATHA IN THE MANAGEMENT OF CHRONIC KIDNEY DISEASE (CKD)-A CASE STUDY - Amilkanthwar, *R.H.; Dawale, Pandit; Keshavrao, Gindewar Ajay (International Journal of Ayurveda and Pharma Research, 2017)
Kidney is the most useful organ for maintain the homeostatic balance of body fluids by removing waste out of body. Chronic kidney disease (CKD) refers to irreversible deterioration in renal function which develops over period of years. In CKD treatment of choice is dialysis and renal transplantation which is more cost and complexity cant afford for every CKD patients and few patients are able to obtain adequate treatment for kidney disorders. Therefore required safe and alternative therapy is needed which helpful in reducing the requirement of dialysis and the renal transplantation. Punarnava can rejuvenates the dying cell and help to revive the dying organ of the body. As the Gokshura has diuretics action which is beneficial in CKD for decrease the oliguria and Rasayana properties of Gokshura which can be prevented and repair by Rasayana drug by their antioxidative properties. Basti is the treatment mostly effective on Pakvashaya in which urine formation carried out and Punarnavdi basti rejuvenates the dying cell and improve in renal function. In this study first 12 days patients given Punarnavadi basti and Kwath then only Kwath is continues and the result is improved in renal function by reducing the value of serum creatinine and blood urea. From we suggestive that Punarnavadi kshir basti and Punarvadi kwath in chronic renal failure the improvement in renal function and general condition is observed.